The Impact of Various Reactive Oxygen Species on the Formation of Neutrophil Extracellular Traps. (8th March 2012) - Kirchner, Tina; Möller, Sonja; Klinger, Matthias; Solbach, Werner; Laskay, Tamás; Behnen, Martina
Abstract : The formation of neutrophil extracellular traps (NETs) depends on the generation of reactive oxygen species (ROS). Previous studies revealed that both NADPH oxidase and myeloperoxidase (MPO) are required for NET release. However, the contribution of various ROS as well as the role of mitochondria-derived ROS has not been addressed so far. In the present study we aimed to investigate in a systematic and comprehensive manner the contribution of various ROS and ROS-generating pathways to the PMA-induced NET release. By using specific inhibitors, the role of both NADPH oxidase- and mitochondria-derived ROS as well as the contribution of superoxide dismutase (SOD) and MPO on the NET release was assessed. We could demonstrate that NADPH oxidase function is crucial for the formation of NETs. In addition, we could clearly show the involvement of MPO-derived ROS in NET release. Our results, however, did not provide evidence for the role of SOD- or mitochondria-derived ROS in NET formation.